Simple Mathematical and Computational Wear Model for Ultra-High-Molecular-Weight Polyethylene Total Hip Replacements - K. H. S. Chan; T. Pearce; R. W. Blake; L. Chow; S. Wu; F. Wong; J. Li (Applied Bionics and Biomechanics)
Ultra-high-molecular-weight polyethylene is an important constituent of hip implants. Surgical revisions are required because of implant loosening and osteolysis (destruction or resorption of bone tissue). We develop a mathematical and a computational model to determine implant life (defined as the time when 20% of the implants operating at a given wear rate is revised) based on wear rates and apply them to the data of Sochart (Clin Orthop Relat Res, 363:135–50, 1999). No significant difference was found between mathematical and computational model predictions (14.8 and 14.7 years, respectively) from the actual value of 15.0 ± 3.9 years (X¯ ± 2SE; P > 0.05). We find that an increase in cross-linking does not decrease implant life greatly. However, a large decrease in implant life occurs with an increase in surface roughness, cycles per year and body weight or a decrease in contact stress and femoral head radius.